A visual analysis on the humanized design of the interiors of an HIV testing center - Teaño, Deanna Sophia D. (College of Home Economics, University of the Philippines Diliman, 2021)
The research expounded on humanization as a framework considered in the design of the interiors of LoveYourself Anglo Community Testing Center, located in Mandaluyong City, Metro Manila. Specifically, the study examined the elements of the interior that fall under the chosen parameter, recorded the perception of the respondents based on the gathered images of LoveYourself Anglo, and evaluated the space according to the concepts of the theoretical framework. The proposal of Victoria Bates (2018) was utilized as the central basis of the inquiry, which defined humanized medical spaces to aim being non-biomedical, non-institutional, and non-technological. The inquiry is qualitative in nature which acquired results through the visual survey prepared by the researcher. The participants for the study were selected through purposive sampling whereby the scope requires that they 1) classify as young adults and 2) have experienced undergoing HIV testing service. Following the feedback of the respondents, the results showed that LoveYourself Anglo showed manifestations of humanization in the testing center. This was established through homeliness, diversion, and coziness as reflected in the furniture selection, material specifications, colors, decorative elements, and the provision of a multi-purpose space. The study also expounded on the significance of the eight dimensions that factor in the humanization of healthcare as proposed by Todores et. al. (2009), where togetherness and sense of place have been exhibited. Based on the results from the study, the respondents recommended that the space may benefit from improvement in the nature-related implements and the artistic applications in the center. The obtained information reflected that LoveYourself Anglo was seen to have achieved comfort and characteristics of residential design that allowed a broader sense of healing which a utilitarian direction in medical design tend to overlook. For further studies, the following are recommended: on-site participation from the respondents, facilitating a gender-specific survey, and surveying from visual-related experts